PENGARUH EKSTRAK AIR RUMPUT TEKI (CYPERUS ROTUNDUS) TERHADAP PERTUMBUHAN DAN KANDUNGAN KLOROFIL PADI GOGO VARIETAS INPAGO 8 - Agustin, Mia A.; Zulkifli, Zulkifli; Handayani, Tundjung T.; Lande, Martha L. (Jurnal Penelitian Pertanian Terapan, 2018)
The purpose of this research is to know whether the aqueous extract of purple nutsedge(Cyperus rotundus) have an effect on the growth and chlorophyll content of upland riceseedling of Inpago 8 varieties. This research was conducted at Botanical Laboratory ofBiology Department Faculty of Mathematics and the Natural Sciences University ofLampung from September to October 2017. The experiments were carried out in a completerandomized design with the main factors being aqueous extract of purple nutsedge with 5 level : 0% v / v (control), 5% v / v, 10% v / v, 15% v / v, and 20%v/v. Parameters measuredwere shoot length, fresh weight, dry weight, relative water content, and total chlorophyllcontent of rice seedling. Homogeneity of variance was determined by the Levene test at 5%significant level. Analysis of variance and Tukey HSD test is done at 5% significant level.The results showed that the concentration of extract correlated quadratic with shoot lengthwhere the maximum shoot length was 3.9 cm at 10% extract concentration. Fresh weight andrelative water content maximum were 73.21 mg and 76% respectively at concentrations of14% and 10%. The minimum total chlorophyll content was 0.47 mg / g tissue at aconcentration of 11%. There was no significant effect on the dry weight of the seedling.From the results of the study, it was concluded that the extract of purple nutsedge at aconcentration below 14% was a growth stimulator, but it was an inhibitor of chlorophyllbiosynthesis.Keyword: Chlorophyll, Growth, Upland rice variety Inpago 8, Purple nutsedge